Value Predicate Analysis: A Language‐Based Tool for Diagnosing Behavioral Tendencies of Religious or Value‐Based Groups in Regions of Conflict. Issue 1 (9th December 2018) - Ochs, Peter; Faizi, Nauman; Teubner, Jonathan; Moulvi, Zain
Abstract: This article introduces a language‐based tool for addressing the role of religion in violent conflicts. Value predicate analysis (VPA) is an easily transportable, relatively uncomplicated early warning tool for measuring the probable near‐future behavior of modest‐sized religious groups in settings of potential conflict. We show that it is possible to identify a range of nine types of probable group behavior toward other groups. This approach significantly refines current binary assessments of violent/not‐violent group conduct. The authors (1) provide a warrant for diagnosing religion‐group behavior through performative analysis; (2) present a theoretical overview of VPA; (3) summarize their research, data analysis, and field collection methods; (4) present field test results; and (5) conclude with recommendations for further research.